Verification of the method for reconstruction of individualized external exposure doses to persons living in a contaminated territory with radionuclides - Kulikovich, Dmitry; Vlasova, Natalie; Visenberg, Yuliya; Kuznetsov, Boris (Journal of the Belarusian State University. Ecology, 2024)
Correct assessment of individual exposure doses to the population is an integral component for conducting radiation epidemiological studies to establish the dose-effect relationship and identify the most exposed groups of the population. At the same time, difficulties in assessing individual external exposure doses arise when there is a lack or absence of individual dosimetric control data. In this regard, the assessment of external exposure doses of persons living in areas contaminated with radionuclides is carried out by reconstructing the latter on the basis of official methodological documents. Due to the over conservative nature of exposure dose reconstruction methods, many of them simply don't correspond to the task of dose individualization, since they only allow estimating average values ​​within a locality, and many lead to significant errors of 300% or more. Based on the above, we have previously developed and proposed a new method for reconstructing individualized external exposure dose, which allows us to take into account not only the direct factor of dose formation - the surface contamination density by 137Cs, but also “indirect” factors, such as occupation, gender and age of the individual. To assess the adequacy of the method we developed and the possibility of using it to reconstruct individualized external radiation doses we carried out its verification. A research sample was formed based on individual dosimetric control data of residents of the Mogilev region for 2005 and 2006. The sample was formed taking into account the representativeness by type of occupation of the rural population, by gender and age, which have a statistically justified influence on the formation of the individual external exposure dose. The result of a comparative analysis of reconstructed doses with IDC data showed that for the sample as a whole for each year and for occupational groups, the estimated data and IDC data are completely comparable, the estimation error did not exceed 11%. Thus, verification of the developed method for reconstructing individual external exposure doses to persons living in a radioactively contaminated area showed that the proposed method can be used when there is insufficient amount of IDC data or, in their absence, to predict individual external exposure doses to persons living in a radioactively contaminated area.
Keywords: external exposure dose; individual dosimetric control; individualized dose; informative factor-sign; occupational group; regression model